아파트 단지 조경요소별 입주민의 가치인지도 대비 공사비 측정의 상대적 적정성 분석 - 공공기관 시행 수도권 분양아파트를 중심으로 - 박상진; Park Sang-jin; 조세환; Cho Se-hwan (한국조경학회지, 2016)
본 연구는 공기업에서 측정하는 공공주택단지 조경공사 비용이 `수요자의 요구에 부응하여 투입되고 있는가?`라는 의문에서 출발하였다. 주민들이 조경요소에 대해 인식하고 있는 가치도에 부응하여 조경공사비가 적정한 비율로 투입되고 있는지 여부를 분석해봄으로써 향후 아파트단지 조경공사비 측정의 효율성을 높이기 위한 기초자료 제시를 목적으로 수행되었다. 본 연구는 관련 이론 고찰과 함께 `J공사`에서 2004년에서 2012년까지 9년간 시행한 수도권 분양 아파트단지7곳 입주자들을 대상으로 한 설문조사 분석을 통해 수행하였다. 특히 가치인지도 비교 분석에서는 조경요소의 계층을 구분하여 계층별 비율에 근거, 실제 투입된 공사비를 기준으로 비교분석하는 방법을 사용하였다. 본 연구의 결과는 다음과 같다. 첫째, 입주민들의 아파트 조경에 대한 관심도는 높았고, 조경에 대한 가치도 역시 높게 두고 있었으나, 현실적인 만족도는 상대적으로 낮은 것으로 나타났다. 둘째, 조경요소에 대한 입주민들의 가치도는 `시설물` 요소보다 `식재` 요소에 더 높은 가치를 부여하고 있는 것으로 나타났다. 셋째, 입주민들이 조경요소들에 대해 인지하고 있는 가치도와 공사비투입금액을 상호 비교한 결과, 조경요소에 따라 1.25에서 52배까지 가치도와 실제 투입 공사비와의 비율이 차이가 있는 것으로 나타났다. 넷째, 이상의 결과는 가치도와 투입공사비와의 상대적 비율에서 차이가 난다는 것은 공사비 측정 과정에서 입주민의 수요에 부응하지 못하고 있다는 것과 동시에 공사비 투입의 효용성이 낮다는 것을 보여주고 있었다. 따라서 효율적인 아파트 조경공사비 측정을 위해서는 지금까지 해 오던 조경공사비 비율을 그대로 적용하는 관행적인 방식의 틀을 벗어나, 각각의 조경요소들에 대한 입주민들이 느끼는 가치 등 수요자 기반의 미시적 차원에서 조경공사비투입계획을 수립하고 집행하여야 할 것으로 나타났다. This study started with the question, “Is the cost of landscape construction work in residential areas measured by public enterprises, `in response to the needs of consumers?`” The study analyzed whether the landscape construction expenditure is being introduced at an appropriate ratio according to the value the residents have regarding landscape elements. Following this, research was conducted for the purpose of providing basic data for improving the efficiency of formulating apartment landscape construction costs in the future. This research proceeded based on a questionnaire survey of residents of apartments, and the content of the questionnaire used frequency analysis and descriptive statistics research methods. To take a look at a comparative analysis of value recognition, in particular, a comparative analysis was performed based on the actual input cost based on the ratio of landscape elements by layer. Conclusions were found as follows: First, the degree of interest in the apartment landscape of the tenants was high, and the value of the landscape was high but realistic satisfaction appeared comparatively low. Second, the awareness of residents` values regarding landscape elements appeared to give “plantings” more value than “facilities”. Thirdly, as a result of a mutual comparison between the values recognized by the resident regarding landscape elements and the construction input fee, depending on the landscape elements, it appeared that there is a difference in the ratio of up to 52 times from 1.25. Fourth, the fact that there is a difference in the relative proportion of value recognition and inputting construction cost indicates that it is not possible to respond to the needs of tenants during the construction cost development process. It also shows that the utility of inputting construction costs is low. Therefore, a macro-level examination such as reflecting the existing inflation rate is necessary to develop the efficient landscape construction cost of apartment such as the awareness of the value of the residents regarding landscape elements, out of the customary construction cost formulation method based on the microscopic dimensions of the consumer side.